Estimating the herd immunity effect of rotavirus vaccine. Issue 32 (31st July 2015) - Pollard, Suzanne L.; Malpica-Llanos, Tanya; Friberg, Ingrid K.; Fischer-Walker, Christa; Ashraf, Sania; Walker, Neff
Abstract Introduction Diarrhea is one of the leading causes of death in children under 5, and an estimated 39% of these deaths are attributable to rotavirus. Currently two live, oral rotavirus vaccines have been introduced on the market; however, the herd immunity effect associated with rotavirus vaccine has not yet been quantified. The purpose of this meta-analysis was to estimate the herd immunity effects associated with rotavirus vaccines. Methods We performed a systematic literature review of articles published between 2008 and 2014 that measured the impact of rotavirus vaccine on severe gastroenteritis (GE) morbidity or mortality. We assessed the quality of published studies using a standard protocol and conducted meta-analyses to estimate the herd immunity effect in children less than one year of age across all years presented in the studies. We conducted these analyses separately for studies reporting a rotavirus-specific GE outcome and those reporting an all-cause GE outcome. Results In studies reporting a rotavirus-specific GE outcome, four of five of which were conducted in the United States, the median herd effect across all study years was 22% [19–25%]. In studies reporting an all-cause GE outcome, all of which were conducted in Latin America, the median herd effect was 24.9% [11–30%]. Conclusions There is evidence that rotavirus vaccination confers a herd immunity effect in children under one year of age in the United States and Latin American countries. Given the high variability in vaccine efficacy across regions, more studies are needed to better examine herd immunity effects in high mortality regions.